2006
DOI: 10.1007/s10641-006-9067-7
|View full text |Cite
|
Sign up to set email alerts
|

Food habits of the shortfin mako, Isurus oxyrinchus, off the southwest coast of Portugal

Abstract: The shortfin mako, Isurus oxyrinchus, is caught in the eastern North Atlantic as a regular bycatch of the surface-drift longline fishery, mainly directed towards swordfish, Xiphias gladius. Stomachs of 112 shortfin mako sharks, ranging in size from 64 cm to 290 cm fork length, showed teleosts to be the principal component of the diet, occurring in 87% of the stomachs and accounting for over 90% of the contents by weight. Crustaceans and cephalopods were also relatively important in this species' diet, whereas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
44
0
6

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(53 citation statements)
references
References 23 publications
3
44
0
6
Order By: Relevance
“…This may happen during the process of fishing and to the opportunistic behavior of these sharks. The absence of elasmobranchs in the diet of I. oxyrinchus helps to corroborate results obtained by Maia et al (2006). As Pikitch et al (2005) state, this absence may be credited to the low densities such sharks and other ones present in the oceanic environment, when compared to more complex habitats.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…This may happen during the process of fishing and to the opportunistic behavior of these sharks. The absence of elasmobranchs in the diet of I. oxyrinchus helps to corroborate results obtained by Maia et al (2006). As Pikitch et al (2005) state, this absence may be credited to the low densities such sharks and other ones present in the oceanic environment, when compared to more complex habitats.…”
Section: Discussionsupporting
confidence: 74%
“…As Pikitch et al (2005) state, this absence may be credited to the low densities such sharks and other ones present in the oceanic environment, when compared to more complex habitats. Other large predators, such as X. gladius, should also be considered as potential prey for I. oxyrinchus (Stillwell & Kohler 1982, Maia et al 2006, but this fact was not observed in this study.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…These observations are consistent with longline catches of longfin makos in that most captures occur during overnight sets with baits set at depths of 0-220 m below the surface (Dodrill and Gilmore, 1979;Queiroz et al, 2006;Hemida and Capapé, 2008;Bustamante et al, 2009). Satellite tracking results for its congener, the shortfin mako, indicate a similar DVM pattern, but shortfin makos do not appear to have as great a tolerance for depth and cold temperatures.…”
Section: Diel Vertical Movementsupporting
confidence: 62%
“…The longfin mako is a global oceanic species that inhabits both tropical and subtropical waters (Compagno, 2001) but also ranges into temperate seas (Queiroz et al, 2006;Bustamante et al, 2009;Mucientes et al, 2013). In the western Atlantic Ocean, the longfin mako has been documented in the Gulf Stream off the eastern United States, off Cuba's northern coast, as far south as southern Brazil (Compagno, 2001), and as far north as Georges Bank (Kohler et al, 1998).…”
mentioning
confidence: 99%